THE FEATURES OF PARENTAL COMPETENCE IN THE FAMILIES WITH DIFFERENT AGES CHILDREN - Gribanova, Diana; Ivanova, Svetlana; Minina, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article discusses the concept of parental competence. This concept is new for Russian psychology, therefore, the emphasis in the theoretical analysis is done on the English concept. The results of a study of parenting in families with children of different ages: early, preschool and primary school are analyzed. The author's questionnaire was developed for this study, which differ for different ages children parents. A comparison of the results of the research of parents is made. Difficulties related to the procedure for the research of early and preschool ages children parents are marked. The specificity of the parents` of children who are not attending school responses is indicated. The conclusion about the features of parental competence and need for training of parents` of different ages children knowledge and skills on parenting are done. These results demonstrate the need for the creation of parental universities based on public and private educational institutions to increase the level of parental competence.